NANOSTRUCTURE OF RENEWABLE OXYGENATED FUELS PARTICULATE MATTER - Preechar Karin; Yutthana Songsaengchan; Songtam Laosuwan; Chinda Charoenphonphanich; Nuwong Chollacoop; Katsunori Hanamura (My University, 2012)
This paper describes a part of an ongoing research project in diesel Particulate Matter (PM) reduction by using renewable oxygenated fuel. In order to achieve the particulate matter reduction, physical structure and aggregation behavior should be investigated for better understanding of designs and configurations of Diesel Particulate Filter (DPF). The nanostructures of diesel and biodiesel PMs were investigated by using a Scanning Electron Microscopy (SEM) and a Transmission Electron Microscopy (TEM) for better understanding. The primary size distributions as well as particulate structures were presented by means of scanning images. The average primary sizes of diesel and biodiesel fuels PMs are approximately 50-60 nm and 30-40 nm, respectively. The average carbon platelet sizes of diesel and biodiesel PMs are in the range of 0.5-3.0 nm. In addition, Thermo-gravimetric Analysis (TGA) was used to investigate chemical kinetics of particulate matter oxidation. The apparent activation energies of oxygenated hydrocarbon, diesel hydrocarbon and carbon oxidation are approximately 91 kJ/mol, 130 kJ/mol and 155 kJ/mol, respectively.
Keywords: Air Quality and Health Impacts